A FRAMEWORK FOR KNOWLEDGE TRANSFER IN PERSONAL LEARNING ENVIRONMENT IMPLEMENTATIONS - MOHAMAD SANI, NUR SYAFIQAH (2018)
Knowledge transfer has been the common practice that happens daily through an individuals’ personal learning process. However, knowledge transfer is rarely being evaluated due to the fact that there are lack of standardized guidelines or frameworks that focussed on the ideal implementation of the process, specifically in personal learning context.